2003
DOI: 10.1080/0036554021000026981
|View full text |Cite
|
Sign up to set email alerts
|

Zanamivir: a Significant Reduction in Viral Load During Treatment in Military Conscripts with Influenza

Abstract: A randomized, double-blind, placebo-controlled, parallel-group trial performed at 5 residential units of the Finnish Defence Forces was conducted to assess the antiviral activity, efficacy and safety of inhaled zanamivir for the treatment of naturally acquired influenza. Conscripts were recruited within 2 d of onset of typical influenza symptoms and received inhaled zanamivir 10 mg via a Diskhaler twice daily for 5 d or matching placebo. Time to alleviation of clinically significant symptoms of influenza was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 18 publications
1
34
0
Order By: Relevance
“…Similarly, use of zanamivir for treatment of naturally occurring influenza in military conscripts significantly reduced the mean viral load after 48 h of treatment compared with placebo (P < 0.001; Table 4). 36 An assessment of two zanamivir phase II trials showed a trend towards reduction in duration of shedding and titers; however, these reductions were significant for only one study. 38 There is a paucity of studies comparing the efficacy of oseltamivir and zanamivir in reducing viral shedding.…”
Section: Treatment Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, use of zanamivir for treatment of naturally occurring influenza in military conscripts significantly reduced the mean viral load after 48 h of treatment compared with placebo (P < 0.001; Table 4). 36 An assessment of two zanamivir phase II trials showed a trend towards reduction in duration of shedding and titers; however, these reductions were significant for only one study. 38 There is a paucity of studies comparing the efficacy of oseltamivir and zanamivir in reducing viral shedding.…”
Section: Treatment Studiesmentioning
confidence: 97%
“…)5,6,8,33,35,36 . Hayden et al6 demonstrated that treatment with oseltamivir 20 mg, 100 mg, or 200 mg BID or 200 mg OD for 5 days significantly reduced both the viral titer and the median duration of viral shedding in the pooled oseltamivir treatment group (n = 56) compared with placebo (n = 13;…”
mentioning
confidence: 99%
“…Zanamivir has been shown to interact with a group of amino acids in the active site of neuraminidase which blocks its action, preventing release and spread of the newly formed virons [1]. Zanamivir has been shown to be effective in preventing, controlling, or rapidly reducing: illness with fever [2], influenza in family contacts [3], nursing home outbreaks [4], elevated body temperature [5], and viral load [6]. In vitro data suggests that zanamivir is a highly potent inhibitor of several strains of influenza A [7]; however, extremely low bioavailability limits efficacy following an * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…In the influenza studies examined, the median number of days until resolution of the illness in the placebo groups was 4 to 8 days after the beginning of the study period. 12,[14][15][16][17][18][19][20][21][22][23]25 If patients are being treated around the end of the disease course, the data may therefore be inconclusive.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…As a result, we retained 11 primary clinical studies that met the criteria of being an RCT examining the efficacy of NAI drugs in treating naturally occurring influenza or influenza-like illness (ILI) in non-highrisk, healthy adult populations. 12,[14][15][16][17][18][19][20][21][22][23] This subset was chosen in order to establish the common, reproducible design elements in the most recent, and most frequently cited and reviewed influenza clinical or antiviral trial reports. Although we excluded trials on high-risk groups or prophylaxis, as well as studies lacking a control arm, these trials are other important avenues of research for CAM therapies, and should be followed up on once a firm foundation for primary clinical treatment trials has been established.…”
mentioning
confidence: 99%